Causes and Factors Associated with Neonatal Seizure and its Short-term Outcome; A Retrospective Prognostic Cohort Study - Nemati, Hamid; Karimzadeh, Parvaneh; Fallahi, Minoo (Iranian Journal of Child Neurology, 2018)
Abstract Background: Neonatal seizures are common, difficult to diagnose and treat, and associated with a great mortality rate and long-term risk of neurodevelopmental impairments. We aimed to determine the etiology, clinical presentation, and neurodevelopmental outcome of neonatal seizures. Methods: In this cross-sectional study, 88 neonates, aged < 28 days, who were admitted to Mofid Children’s Hospital, Tehran, Iran, from September 2011 to 2013 with the initial diagnosis of seizure were included by convenient sampling method. Data, including age, gestational age, birth weight, Apgar of the fifth minute, neonatal intensive care unit (NICU) admission, family history, type, cause, and age of seizure, EEG and paraclinic findings, anticonvulsant used for treatment, neurodevelopmental status, and the final outcome, were collected from medical records and the missed cases were completed by phone calls. The frequency and association of variables were analyzed using SPSS software. Results: Among neonates with seizures, 67% were male, 79.5% were born term, and 72.7% had normal birth weight. The most common type of seizure was multifocal clonic seizures (45.5%). The main diagnosis in neonates with seizures was hypoxic-ischemic encephalopathy (HIE) (23.9%) and hypoglycemia (10.22%). The mortality rate was 11.36% during a mean follow-up period of 21.4±6.4 months. Neurodevelopmental assessments showed that 64% were normal, 27% had global delay, and 9% had motor delay. Positive family history of epilepsy (P=0.006), low Apgar score (P=0.002) and epilepsy (P<0.001) were significantly associated with adverse neurodevelopmental outcome. Conclusion: Since HIE and hypoglycemia were the most common cause of neonatal seizures in the present study, efforts should be made to improve care during delivery and early breastfeeding. Keywords: Newborn; Seizure; Etiology; Neurodevelopmental outcome